NKp30 isoforms in patients with chronic hepatitis C virus infection. Issue 2 (8th July 2015) - Mantovani, Stefania; Mele, Dalila; Oliviero, Barbara; Barbarini, Giorgio; Varchetta, Stefania; Mondelli, Mario U.
Summary: Natural killer (NK) cells play an important role in virus infection, their action being regulated by several activating and inhibitory receptors. The NKp30 activating receptor and its isoforms have recently emerged as important determinants of efficient NK cell responses. We determined the relative proportions of NKp30 isoforms in patients with chronic hepatitis C virus (HCV) infection and healthy donors (HD). NK cell function (degranulation and cytokine production) and correlations with clinical parameters were assessed following unsupervised hierarchical clustering of patients according to isoform expression. NKp30 receptor expression on NK cells and all isoforms were reduced in HCV‐infected patients. Patients were clustered into two groups: the HCV‐1 group had similar isoform expression to the HD group, whereas the HCV‐2 group had lower expression. The latter showed a better functional activity, and a higher proportion of the activating a isoform and of the NKp30 isoform a/c ratio compared with the HCV‐1 cluster. There was a positive correlation between the activating a isoform and liver stiffness and an inverse relationship between the immunosuppressive c isoform and the fibrosis 4 score, suggesting a potentially important role of NKp30 isoforms in influencing liver damage and ensuing fibrosis.